A Novel, Synthetic, Neuroactive Steroid Is Effective at Decreasing Depression-Like Behaviors and Improving Maternal Care in Preclinical Models of Postpartum Depression - Melón, Laverne; Hammond, Rebecca; Lewis, Mike; Maguire, Jamie (Frontiers in Endocrinology, 2018)
Preclinical testing of treatments for postpartum depression (PPD) has been limited due to the lack of available animal models of such a complex disorder. To address this limitation, our laboratory has generated unique preclinical mouse models that exhibit abnormal postpartum behaviors. Mice with a loss or reduction in the expression of the GABAA receptor (GABAAR) δ subunit (Gabrd-/- or Gabrd+/-, respectively) and mice that lack the K+/Cl- co-transporter, KCC2, specifically in corticotropin-releasing hormone (CRH) neurons (KCC2/Crh mice) exhibit depression-like behaviors restricted to the postpartum period and deficits in maternal care, which serve as useful tools for testing novel therapeutic compounds. Utilizing these preclinical models, we tested the ability of a novel, synthetic, neuroactive steroid developed by SAGE Therapeutics, SGE-516, to improve abnormal postpartum behaviors. Gabrd-/-, Gabrd+/-, and KCC2/Crh dams treated with SGE-516 (450 mg/kg chow) during late pregnancy exhibit a decrease in depression-like behaviors and improvements in maternal care at 48 hrs postpartum. Interestingly, acute treatment with SGE-516 also exhibits robust therapeutic effects in these preclinical PPD models. We previously discovered abnormal stress reactivity associated with hypothalamic-pituitary-adrenal (HPA) axis dysregulation associated with depression-like behaviors in the preclinical PPD models, evident from an increase in stress-induced corticosterone levels and dephosphorylation and downregulation of KCC2 in the paraventricular nucleus of the hypothalamus (PVN) during the peripartum period. Here we demonstrated that SGE-516 treatment is sufficient to prevent the stress-induced increase in corticosterone and dephosphorylation and downregulation of KCC2 in the PVN. In contrast, and consistent with the distinct pharmacology of SGE-516 compared to benzodiazepines, treatment with clobazam (250mg/kg chow) did not alter the depression-like phenotype or deficits in maternal care observed in these preclinical models of PPD. These findings are consistent with the positive double-blind, randomized, placebo-controlled trial findings of a similar compound, brexanolone, in the treatment of patients with postpartum depression. Further, these findings validate the use of these preclinical models of PPD for screening novel compounds for the treatment of postpartum depression.